Inclusive cartography: the use of tactile maps by visually impaired students in the teaching of Geography (Research, Society and Development, 2020)
The present work has as its central objective to optimize the teaching of geography for students with visual impairment through the use of cartography through the elaboration and use of tactile maps. We assume that the application of conventional maps does not meet the needs of blind or partially sighted people, thus, understanding the importance of cartography in the daily lives of individuals, we seek viable alternatives that enable the inclusion of these students in the classroom. During the interventions carried out in conjunction with the Pedagogical Residency program at the nucleus of the Federal University of Rio Grande Norte (UFRN), in partnership with the Padre Miguelinho Institute - Natal / RN-Brazil, we made maps adapted to use in Geography classes for students who do not have vision as perception. In view of this, we propose as a methodological procedure the construction of teaching materials taking into consideration the description of the difficulties faced by the students, which during the development of the work, were heard in order to succeed in the process of their inclusion in regular classes. After a long process and countless attempts, a map was made with different textures, high relief ink and completely subtitled in Braille. By applying the material produced during the visits to the school's multifunctional resource room, the results were promising, both the low vision student and the student with total blindness could read the map alone, only under our supervision.